A baculovirus-mediated expression system for the analysis of HaSV RNA packaging - Mendes, Adriano (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
The Helicoverpa armigera stunt virus (HaSV) is a member of a family of small nonenveloped (+) ssRNA insect viruses currently known as the Tetraviridae. This family is unique in terms of the T=4 quasi-symmetry of its capsid particles and the unusually narrow host range and tissue tropism. Assembly of tetraviral particles has been well characterised and involves the combination of 240 copies of a single capsid precursor protein (VCap) into a procapsid followed by autoproteolytic cleavage to yield the major (Î²) and minor (Î³) capsid subunits within the mature particle. HaSV has two genomic RNAs, RNA 1 encoding the replicase and RNA 2 encoding VCap and p17, the ORF of which lies upstream of and overlaping with the 5' end of the VCap ORF. Prior to this study, Vlok (2009) used a plasmid expression system to study RNA packaging in HaSV VLPs assembled in Spodoptera frugiperda 9 (Sf9) cells co-expressing p17 and VCap. The study showed that the p17 ORF was required for the packaging of RNA 2 during capsid assembly but it was unclear whether p17 expression was required for packaging. In addition, expression from the transfected plasmids was sub-optimal affecting both the yield of VLPs and the detection of p17. The aim of this study was to use the plasmid system to test whether p17 expression was required for plasmid-derived VLP RNA packaging and then develop a baculovirus-mediated system to test this hypothesis. By using a plasmid in which the start codon of p17 was mutated, it was shown that p17 expression was required for RNA 2 packaging into plasmid-VLPs. For the baculovirus system, four recombinant baculoviruses based upon the pFastBac Dual expression system, were constructed. These included Bac20, expressing wild type RNA 2, Bac21, RNA 2 with p17 silenced, Bac23, RNA 2 and p17 expressed on a separate transcript and Bac24, RNA 2 with p17 silenced plus p17 expressed on a separate transcript. Assembly of VLPs was more efficient using the baculovirus expression system and p17 expression was observed in cells infected with Bac20, Bac23 and Bac24, but not Bac21. In contrast to the plasmid-VLPs, bac-VLPs did not require p17 for the encapsidation of RNA 2. In addition to RNA 2, Bac23 and Bac24 packaged the p17 mRNA transcribed separately from RNA 2. This insinuated that bac-VLPs may be packaging RNA non-selectively. It was proposed that p17 may play a role in packaging in an RNA-limiting environment (plasmid system) but functioned differently when viral RNA was in excess (baculovirus system). This data points to the importance of developing a replication system for the analysis of the packaging pathways of these viruses and this study has laid down the foundations for such a system in which RNA 1 and RNA 2 can be introduced into a single cell by means of a single recombinant virus.
Keywords: RNA; Baculoviruses; Helicoverpa armigera; Plasmids